2021
DOI: 10.3390/ma14227100
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Walled Cylindrical Shell Storage Tank under Blast Impacts: Finite Element Analysis

Abstract: Thin-walled cylindrical shell storage tanks are pressure vessels in which the walls of the vessel have a thickness that is much smaller than the overall size of the vessel. These types of structures have global applications in various industries, including oil refineries and petrochemical plants. However, these storage tanks are vulnerable to fire and explosions. Therefore, a parametric study using numerical simulation was carried out, considering the internal liquid level, wall thickness, material yield stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This article gives an overview of accident frequencies of atmospheric storage tanks and past accidents described in the open literature to show the possible accidental sequences, underline the most frequent causes involved in explosions of atmospheric storage tank, and highlight the potential consequences of such accidents [22]. In general, within the wide range of accidental explosion types, vapor cloud explosions are a major concern in the petrochemical and petroleum industry [20,[23][24][25][26]. The same applies to LNG process units [27][28][29] and can therefore be adopted to ammonia process units as the main cause for the blast overpressure analysis and design.…”
Section: Characteristics Of Blast Load and Pressure Wave Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…This article gives an overview of accident frequencies of atmospheric storage tanks and past accidents described in the open literature to show the possible accidental sequences, underline the most frequent causes involved in explosions of atmospheric storage tank, and highlight the potential consequences of such accidents [22]. In general, within the wide range of accidental explosion types, vapor cloud explosions are a major concern in the petrochemical and petroleum industry [20,[23][24][25][26]. The same applies to LNG process units [27][28][29] and can therefore be adopted to ammonia process units as the main cause for the blast overpressure analysis and design.…”
Section: Characteristics Of Blast Load and Pressure Wave Propagationmentioning
confidence: 99%
“…However, because tanks have long been designed based on simplified rules and many years of experience, and because finite-element analysis has only been the state of the art for more complex tank analysis problems in the last two decades, blast load analyses of tank structures are still challenging and part of the current research. A large proportion of the analyzed literature uses the simplified dynamic method based on the shockwave propagation described in Section 2.2, which can be applied in LS-DYNA [18] by means of the already mentioned feature *LOAD_BLAST_ENHANCED, for instance [24,26,41]. In contrast, there are several works that adopt a different approach.…”
Section: State Of the Art On Blast Load Analyses Of Tank Structuresmentioning
confidence: 99%
“…At the present stage of the ongoing research in the field of the earthquake resistance of plate and shell structures, a number of relevant studies can be found [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Particularly, in the work proposed by Śliwa et al [47], in order to restore the carrying power of a structure, the problem of repairing the "dents" with carbon fibers was considered, but the issue of the dynamic effects was not investigated.…”
Section: % 36% 52%mentioning
confidence: 99%
“…Moreover, the study proposed by Joniak et al [49] considered the issue of elastic bending, where an analytical formula for critical stresses for open round cylindrical thin shells in a state of pure bending was proposed. Conversely, the work presented by Al-Yacouby et al [50] focused on numerical modeling for the design of operational loads taking into account hydrodynamic pressure. In Hud [51] and Sierikova et al [52], a Finite Element (FE) model of a full-scale steel tank was implemented and calculations were executed under operational loading.…”
Section: % 36% 52%mentioning
confidence: 99%